Mating plan for the production of G21 (G202502) GIFT tilapia TiLV resistant families - Izadi, Fariba; Hamilton, Matthew; Mahmuddin, Mahirah (2025)
This is a mating list for GIFT TiLV resistant families targeted for production in 2025 as part of the WorldFish GIFT tilapia Genetic Improvement Program. It was developed based on genetic analysis to generate EBVs based on challenge test data, optimal selection to identify parental family contributions, marker assisted selection to identify TiLV resistant candidate parents with high harvest weight and mate allocation to minimise inbreeding (adopting assortative mating).